Prediction and multi-criteria-based schemes for seamless handover mechanism in mobile WiMAX networks - Mubarak, Mohammed Awadh Ahmed Ben (2013)
Mobile WiMAX introduces several interesting advantages including last mile wireless access, variable and high data rate, point to multi-point communication, large frequency range and QoS (Quality of Service) for various types of applications. However, mobility in WiMAX system is still an issue when a mobile station (MS) moves and its connection is handed over between base stations (BSs). This thesis focuses on three main stages of the handover procedure in Mobile WiMAX;scanning, cell selection and handover initiation and decision. It introduces four main schemes to optimize the handover mechanism. The first scheme is Mobile Station Movement Direction Prediction (MMDP) based handover scanning that reduces the redundant scanning activities, scanning delay and signalling overhead. Simulation results show that the proposed MMDP scheme reduces handover scanning delay and scanning interval duration by 50% and 25% respectively and reduces the signalling overhead. The second scheme is Hybrid AHP (Analytic Hierarchy Process) and TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution)-based Cell Selection (HATCS) scheme based on a set of multiple criteria. Cell selection is a key element that insures that the QoS and user requirements during and after handover process is met. In the proposed HATSC scheme, the AHP method is uese for criteria weighting, while the TOPSIS method uses for the selection technique based on a multi-criteria decision-making algorithm is proposed. This enables it to meet the MS application requirements based on some criteria such as CINR, BW, and delay. The third scheme is a fuzzy logic-based self-adaptive handover (called FuzSAHO) for handover decision to provide an intelligent self-adaptive handover parameters technique based on received signal strength indicator (RSSI) and MS velocity. Finally, the FuzSAHO decision algorithim is optimized for real-time application, by using a new handover criteria, namely queue length besides RSSI and MS velocity. This new self-adaptive handover scheme for real-time application called RFuzSAHO. Simulation results show that FuzSAHO reduces the ping-pong handover, and handover delay. It reduces the number of handovers by 29.7% and 26.9%, respectively, compared to the conventional RSSI based handover algorithm and the previous worked, mobility improved handover (MIHO) algorithm. In terms of handover delay, FuzSAHO reduce handover delay by 40% and 15% compared to RSSI based-HO and MIHO respectively. Also, it is shown that FuzSAHO enhances the overall handover operation in term of reduced overhead signalling, average E2E packet delay and satisfactory CINR which satisfies network end user requirements. For real-time applications, simulation results show that RFuzSAHO decision algorithm enhances the VoIP quality (Mean Opinion Score, MOS) up to 5.4% compared to FuzSAHO algorithm when the MS velocity is 20m/s.